Factors Affecting Staff Satisfaction in using the Parcel Service Faculty of Liberal Arts, Rajamangala University of Technology Thanyaburi - ดิษฐสอน, จรัสศรี (Journal of Humanities and Social Sciences, Rajapruk University, 2020)
The purpose of this research were to study 1) the level of satisfaction of staff using the parcel service at Faculty of Liberal Arts Rajamangala University of Technology Thanyaburi, 2) Factors affecting staff satisfaction in using the parcel service at Faculty of Liberal Arts Rajamangala University of Technology Thanyaburi, and 3) Problems, obstacles and suggestions to create a guideline for improving the supply management at the Faculty of Liberal Arts Rajamangala University of Technology Thanyaburi This research was a quantitative research. The 100 staff who used the parcel service at Faculty of Liberal Arts Rajamangala University of Technology Thanyaburi was collected using questionnaires. Data was analyzed by percentage, mean, standard deviation, t-test and one-way analysis of variance (One Way ANOVA). The results of the research showed that the satisfaction of staff using the parcel service Faculty of Liberal Arts Rajamangala University of Technology Thanyaburi in the overall level were at the highest level in 3 areas and at the high level 1 aspect, namely the staff officers, staff in the purchase of durable goods Information about the request for supplies and the employment of repairing equipment, respectively. There was no satisfaction difference of Staff with different gender, age, work experience and work experience were satisfied by the use of parcel service at Faculty of Liberal Arts Rajamangala University of Technology Thanyaburi. The problems and obstacles that most users encounter were as follows: 1) Problems with teaching and learning defective equipment due to lack of continuous maintenance. There should have a good system of repair notification which explain the process of sending and repairing equipment with reasonable price. There should have an inventory information that updated on the website for users to be able to study on their own or check the initial procurement information first.